A call for a multifaceted approach to language learning motivation research: Combining complexity, humanistic, and critical perspectives - Pigott, Julian (Studies in Second Language Learning and Teaching, 2012)
In this paper I give an overview of recent developments in the L2 motivation field, in particular the movement away from quantitative, questionnaire-based methodologies toward smaller-scale qualitative studies incorporating concepts from complexity theory. While complexity theory provides useful concepts for exploring motivation in new ways, it has nothing to say about ethics, morality, ideology, politics, power or educational purpose. Furthermore, calls for its use come primarily from researchers from the quantitative tradition whose aim in importing this paradigm from the physical sciences appears to be to conceptualize and model motivation more accurately. The endeavor therefore remains a fundamentally positivist one. Rather than being embraced as a self-contained methodology, I argue that complexity theory should be used cautiously and prudently alongside methods grounded in other philosophical traditions. Possibilities abound, but here I suggest one possible multifaceted approach combining complexity theory, a humanistic conception of motivation, and a critical perspective.